Kidung Nusaraya: Penciptaan Komposisi Musik berlandaskan Konsep Multikulturalisme Nasionalistik - Slamet, R Chairul (Institut Seni Indonesia Yogyakarta, 2010)
Music Composition based on the Concept of Nationalistic Multiculturalism. This paper aims at analyzing textually the music composition of Kidung Nusaraya. Kidung or tembang (Javanese) means a song, but then the meaning changes into 'something beautiful'.For that reason, all songs or something beautiful can be called as a kidung, including the instrumental music composition entitled Nusaraya. The word Nusaraya is related to the word Nusantara or Indonesia that is abundant with various culture and art potentials; a nation that must realize its potentials including the music to be promoted nationally and internationally.Viewed from the musical perspective, the slogan Bhinneka Tunggal Ika shows that Indonesians are very open in enriching their national music because of their idiomatic variation. The orchestra symphony composition of Nusaraya presents a combination between some Western instruments with the instruments of Nusantara ethnical music to produce beautiful symphonic sounds. Kidung Nusaraya consists of five parts, namely 1) Dialogue, 2) Adaptation, 3) Tolerance, 4) Introspection, 6) Convention, 7) My Country Symphony 8) My Tribute, and 9) My Hope. Keywords: Kidung, music composition, multiculturalism.